The Influence of Good Corporate Governance on the Financial Performance of Insurance Companies Listed on the Indonesia Stock Exchange for the Period 2020-2023 - Afriana, Wendra; Kurniawan, Tikkyrino; Mulatsih (Global Writing Academica Researching & Publishing, 2025)
This study aims to analyze the effect of the board of directors and audit committee on the financial performance of insurance companies listed on the IDX in 2020-2023. The sampling technique that will be applied in this study is purposive sampling so as to obtain 16 companies with a total of 64 data which are then averaged into 16 data on insurance companies listed on the IDX in 2020-2023 which match the research criteria. The conclusion obtained from this research is that the board of directors affects financial performance and the audit committee affects financial performance.